2019
DOI: 10.1093/jxb/erz515
|View full text |Cite
|
Sign up to set email alerts
|

Combating stress: the interplay between hormone signaling and autophagy in plants

Abstract: Autophagy is a conserved recycling process in which cellular components are delivered to and degraded in the vacuole/lysosome for reuse. In plants, it assists in responding to dynamic environmental conditions and maintaining metabolite homeostasis under normal or stress conditions. Under stress, autophagy is activated to remove damaged components and to recycle nutrients for survival, and the energy sensor kinases target of rapamycin (TOR) and SNF-related kinase 1 (SnRK1) are key to this activation. Here, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 128 publications
2
49
0
Order By: Relevance
“…Accumulating findings suggest that plant autophagy is regulated by hormone signaling at the transcriptional and posttranslational levels in response to various environmental stresses (Gou et al, 2019; Signorelli et al, 2019; Liao and Bassham, 2020). Specifically, the abscisic acid (ABA) signaling pathway is likely involved in autophagy‐mediated stress responses.…”
Section: Physiological Roles Of Plant Autophagymentioning
confidence: 99%
“…Accumulating findings suggest that plant autophagy is regulated by hormone signaling at the transcriptional and posttranslational levels in response to various environmental stresses (Gou et al, 2019; Signorelli et al, 2019; Liao and Bassham, 2020). Specifically, the abscisic acid (ABA) signaling pathway is likely involved in autophagy‐mediated stress responses.…”
Section: Physiological Roles Of Plant Autophagymentioning
confidence: 99%
“…Conversely, the ABA-activated SnRK2 can phosphorylate RAPTOR, thus inhibiting TOR-mediated autophagy [ 84 ]. These studies revealed that crosstalk between autophagy and ABA signaling is mediated by the phosphorylation modification of corresponding regulators [ 17 ]. GA antagonistically interplays with ABA in multiple biological processes, but little has been known about this antagonism in regulating autophagy.…”
Section: Autophagy Interplays With Plant Hormones Upon Multiple Stmentioning
confidence: 99%
“…A recent study has shown that a high level of SA caused autophagy-mediated PCD in apple, and the phenotype of accelerated PCD during senescence and immunity in atatg5 mutant was through the SA-dependent rather than the intact JA or ET signaling pathway [ 49 ]. Similar to SA, JA also participates in response to various biotic stresses, and the JA-related WRKY genes have already been implicated as mediating autophagy gene expression upon heat stress and fungal pathogen infection [ 17 ]. For example, WRKY33 was not only involved in the JA-mediated signaling pathway to regulate plant resistance to necrotrophic fungal pathogens, but also directly interacted with ATG18a to regulate autophagy in Arabidopsis [ 17 , 91 ], suggesting WRKY33 coordinates the JA signaling and autophagy pathway to regulate the pathogen stress.…”
Section: Autophagy Interplays With Plant Hormones Upon Multiple Stmentioning
confidence: 99%
See 2 more Smart Citations